2009
DOI: 10.1002/sce.20340
|View full text |Cite
|
Sign up to set email alerts
|

Academic preparation in biology and advocacy for teaching evolution: Biology versus non‐biology teachers

Abstract: Despite considerable focus on evolution knowledge-belief relationships, little research has targeted populations with strong content backgrounds, such as undergraduate degrees in biology. This study (1) measured precertified biology and non-biology teachers' (n = 167) knowledge of evolution and the nature of science; (2) quantified teacher preferences for the teaching of creationism in schools; (3) examined the associations among knowledge and belief variables; and (4) contrasted the knowledge and beliefs of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 55 publications
(94 reference statements)
3
95
0
4
Order By: Relevance
“…Unfortunately, studies conducted over the past 25 years have indicated that students have a number of difficulties understanding this concept (Bishop and Anderson 1990;Gregory 2009;Nehm et al 2009;Shtulman 2006). For example, students may assign agency to organisms, suggesting that they can intentionally change themselves in response to changes in their environment, or they may confuse the concept of biological fitness with everyday meanings of the term (Bishop and Anderson 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies conducted over the past 25 years have indicated that students have a number of difficulties understanding this concept (Bishop and Anderson 1990;Gregory 2009;Nehm et al 2009;Shtulman 2006). For example, students may assign agency to organisms, suggesting that they can intentionally change themselves in response to changes in their environment, or they may confuse the concept of biological fitness with everyday meanings of the term (Bishop and Anderson 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Those who had the greatest levels of acceptance of evolution based on their MATE scores were both above 95% on a 100% scale, which would imply greater knowledge and understanding of both evolution and the nature of science. Despite this, they held similar, if not the same, misconceptions as individuals at the other levels of acceptance (Nehm, Kim, & Sheppard, 2009). An interesting commonality within this group was the ability to separate scientific knowledge of evolution from personal religious beliefs.…”
Section: Discussionmentioning
confidence: 91%
“…(religiosity)과 진화수용, 진화지식, 진화흥미 등에 대해 연구한 바 있 으나 (Ha et al, 2012;Nehm et al, 2009) (Lord & Marino, 1993;Nehm & Schonfeld, 2007;Sinatra et al, 2003). 예를 들어, Sinatra et al(2003) …”
Section: 또한 많은 연구들이 학생들의 종교에 관한 믿음의 정도인 종교성unclassified